FROM TOY AND TOOL TO PARTNER AND PERSON: PHENOMENAL CONVERGENCE/DIVERGENCE AMONG GAME AVATAR METAPHORS - Banks, Jaime; Bowman, Nicholas David (AoIR Selected Papers of Internet Research, 2015)
Although avatars broadly include textual screen names or social network profiles, we specifically discuss here the two- or three-dimensional graphic bodies representing players in online games. Emerging perspectives on player-avatar relations suggest that avatar metaphors may be integrated into a comprehensive framework to foster synthesis of avatar characterizations (Authors, 2014). In particular, the notion of player-avatar sociality (Authors, 2015a) suggests that players variably relate to their avatars along a continuum, from a) non-social relations (avatars are mere objects) to b) parasocial relationships (avatars are player extensions; see Authors, 2008), to c) fully social relationships (avatars are autonomous partners in play). The notion of sociality – the degree to which players relate to avatars as they would relate to other people – ostensibly subsumes a range of more discrete avatar metaphors.